2021
DOI: 10.1016/j.ygyno.2021.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Copenhagen Index versus ROMA in preoperative ovarian malignancy risk stratification: Result from the first Vietnamese prospective cohort study

Abstract: Copenhagen Index (CPH-I) can help stratify the risk of ovarian tumor malignancy.• CPH-I is similarly accurate to but simpler than ROMA.• CPH-I could replace ROMA in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
(29 reference statements)
1
6
0
3
Order By: Relevance
“…In their multi-center study, the authors reported that CPH-I showed similar specificity as the established ROMA ® and RMI indices when sensitivity was fixed at 95% (67.3%, 70.7% and 69.5%, respectively). The preoperative performance of CPH-I in comparison to ROMA ® and CA125 alone was further evaluated in several independent studies around the world with similar findings [ 73 , 76 , 77 , 79 , 186 ]. The most recent validation study of the Copenhagen Index illustrated that CPH-I (AUC 0.92; 95% CI: 0.85–0.98) was able to outperform a modified ROMA ® index (AUC 0.54; 95% CI: 0.38–0.69), but was also comparable to a biomarker panel of six serum proteins (AUC 0.90; 95% CI: 0.82–0.97) [ 70 ].…”
Section: Preoperative Diagnosticsmentioning
confidence: 89%
“…In their multi-center study, the authors reported that CPH-I showed similar specificity as the established ROMA ® and RMI indices when sensitivity was fixed at 95% (67.3%, 70.7% and 69.5%, respectively). The preoperative performance of CPH-I in comparison to ROMA ® and CA125 alone was further evaluated in several independent studies around the world with similar findings [ 73 , 76 , 77 , 79 , 186 ]. The most recent validation study of the Copenhagen Index illustrated that CPH-I (AUC 0.92; 95% CI: 0.85–0.98) was able to outperform a modified ROMA ® index (AUC 0.54; 95% CI: 0.38–0.69), but was also comparable to a biomarker panel of six serum proteins (AUC 0.90; 95% CI: 0.82–0.97) [ 70 ].…”
Section: Preoperative Diagnosticsmentioning
confidence: 89%
“…Similarly, Tu Tran et al recently reported a sensitivity and specificity of 74.2% and 91.8% for ROMA (cutoff 16.5) and 87.1% and 78.5% for CPH-I (cutoff 1.89), respectively. The authors of the latter work did not find significant differences between the diagnostic performance of ROMA and CPH-I [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis retrieving data from 32 studies showed higher AUC and specificity of HE4 in premenopausal women, compared to CA125 and ROMA [ 33 ]. Other authors report higher AUCs for CPH-I, when compared to ROMA and HE4 in premenopausal women [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ROMA, OVA1 and OVERA have been cleared by the US Food and Drug Administration (FDA) for diagnosing suspicious adnexal mass, but not for screening [ 19 , 23 ]. A promising modification of ROMA is the Copenhagen Index (CPH-I), calculated from CA125, HE4 and patient age, which seems to be equal or superior to ROMA, and does not require knowledge of the patient’s menopausal status [ 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%